Manpower Development: A Tool for Efficiency and Productivity of Employees - Ogundiran, Samuel Ogunwale (NIU Journal of Social Sciences, 2018)
This paper assessed the role of manpower as a tool for efficiency and productivity of employees in organisations. The writer of the paper used manpower development theories to explain the concepts discussed therein. The objectives and benefits of manpower development, manpower planning, training and development, management training and development methods, evaluation and determination of training needs, future of manpower development as well as budgeting for manpower are considerably discussed in the paper. The writer of this paper concluded that as a result of the overall importance and relevance of training in the development of skills and potentials of employees and the growth of an organization, the way the programme is planned, executed and evaluated is very important and it is not just carrying out a training programme but through effective implementation, it must accomplish its purpose as well as achieving the needs which were identified and are expected to be met by the training programme. The writer recommended therefore that organizations of any economy should make training and retraining of employees a priority and that training should be the concern of management and which should make employees perform tasks or jobs for which they were trained, and that management should make available information, finance and material resources which are essential for the implementation of training programme since they provide the employees the necessary skill for effective performance of their jobs and there should be a separate department for training in organization since it's not easy to combine their duties together with those of the personnel department among others. Keywords: Manpower Development, Tool, Efficiency, Employees’ Productivity.